Pengaruh mengunyah permen karet xylitol terhadap timbulnya motilitas usus pasca operasi dengan general anestesi - Djunizar Djamaludin; Eka Yudha Chrisanto (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Xylitol gum chewing to achieve early postoperative restoration of bowel motility after surgery under general anesthesiaBackground: The problem that is often encountered in the use of general anesthesia in major surgery is the Post-Operative Ileus (POI). POI is a temporary loss of gastrointestinal propulsion activity characterized by no sounding of bowel sounds and abdominal discomfort and distension. Providing nutrition oral or enteral when bowel sounds begin to sound has a weakness where it was reported that in this intervention the incidence of bloating, nausea and vomiting was mostly experienced by patients who were intolerant of the presence of food in their stomach.Purpose: Knowing the effect of Xylitol gum chewing to achieve early postoperative restoration of bowel motility after surgery under general anesthesiaMethod: A quasi-experimental method with pre-test and post-test in two groups of 20 patients as participants at A. Dadi Tjokro Dipo Hospital Bandar Lampung City recruited and taken by purposive sampling technique, 10 participants as intervention group (treat by chewing xylitol gum) and other of 10 participants as control group.Results: Finding that by a treat of Xylitol gum chewing in postoperative restoration of bowel motility after surgery under general anesthesia took after 2.3 hours while the patients who did not chew xylitol gum occurred 6.8 hours. T-Test showed that p-value was 0.00 that indicated the p-value < 0.05.Conclusion: There was a difference in the occurring time of the intestine motility between control and experiment groups. It is gained that difference is 4.39 hours with p-value = 0.00 which indicated p < 0.05, that there was an effect of chewing gum containing xylitol on the occurrence of post-operative intestine motility after general anesthesia surgery at A Dadi Tjokor Dipo Hospital of Bandar Lampung City. The present study suggests chewing gum is an alternative method to stimulate intestine motility for early post-operation feeding as a low-cost, safe, and tolerable treatment when without contra indication.Keywords: Xylitol gum chewing; Postoperative restoration; Bowel motility; Surgery; General anesthesiaPendahuluan: Masalah yang sering dijumpai dalam penggunaan general anestesi pada pembedahan mayor yaitu Post-Operative Ileus (POI). POI adalah hilangnya aktivitas daya dorong saluran cerna untuk sementara yang ditandai dengan tidak terdengarnya bising usus dan rasa tidak nyaman serta distensi abdomen. Memberikan nutrisi secara oral maupun enteral pada saat bising usus mulai terdengar merupakan memiliki kelemahan dimana dilaporkan bahwa pada intervensi ini kejadian kembung, mual dan muntah paling banyak dialami oleh pasien yang tidak toleran terhadap adanya makanan dalam lambungnyaTujuan: Diketahuinya pengaruh mengunyah permen yang mengandung xylitol terhadap timbulnya motilitas usus pada pasien pasca operasi dengan general anestesi.Metode: Penelitian eksperimen semu dengan pre-test dan post-test group. Jumlah pasien yang akan menjalani operasi elektif dengan menggunakan anestesi umum sebanyak 20 pasien di RSUD A. Dadi Tjokro Dipo Kota Bandar Lampung. Sampel diambil dengan teknik purposive sampling, 10 pasien pasca operasi mengunyah permen karet xylitol dan 10 pasien pasca operasi tidak mengunyah permen karet xylitol.Hasil: Didapatkan motilitas usus timbul 2,3 jam setelah mengunyah permen karet dan 6,8 jam bila tidak mengunyah. Hasil uji t-test didapatkan bahwa p value=0,00 yang berarti nilai p<0,05.Simpulan: Terdapat perbedaan waktu timbulnya motilitas usus pada kelompok kontrol dan kelompok eskperimen sebesar 4,39 jam dan didapatkan nilai p=0,00 yang berarti nilai p<0,05 sehingga Ho ditolak. Oleh karena itu dapat disimpulkan bahwa ada pengaruh pemberian permen karet yang mengandung xylitol terhadap timbulnya motilitas usus pasca operasi dengan general anestesi di RSUD A. Dadi Tjokro Dipo Kota Bandar Lampung. Penelitian ini menunjukkan bahwa mengunyah permen karet adalah metode alternatif untuk merangsang motilitas usus untuk pemberian makan pasca operasi awal sebagai pengobatan yang berbiaya rendah, aman, dan dapat ditoleransi..